Characterizing a regional fishery ecosystem trajectory: the Humpty Dumpty fish tale of the U.S. Gulf of Mexico from 1986 to 2013 - Kilborn, Joshua P. (Frontiers in Marine Science, 2024)
Showcasing the fishery ecosystem trajectory framework, this study seeks to understand the complex interplay between environmental, socioeconomic, and management factors in a large marine ecosystem as they relate to the status, structure, and function of living marine resources over time. Utilizing this framework, a historical accounting of a fishery ecosystem’s shifting stable states can be developed to describe the evolution of resources and identify apparent temporal controls. To that end, approximately three decades of data, spanning 1986–2013, were drawn from the 2017 ecosystem status report for the United States’ Gulf of Mexico (GoM) and used here as a case study. Analyses revealed a capricious system with ten unique fishery regime states over the 28-year period. The fishery ecosystem trajectory was broadly characterized by gradual and persistent changes, likely fueled by exploitation trends. However, a mid-1990s paradigm shift in the dynamics controlling the system-wide organization of resources resulted in an apparent recovery trajectory before leading to continued differentiation relative to its 1986 baseline configuration. This “Humpty Dumpty” ecosystem trajectory signifies permanent alterations akin to the nursery rhyme protagonist’s unrecoverable fall. Anthropogenic factors identified as influential to resource organization included artificial reef prevalence and recreational fishing pressure, while regional effects of the Atlantic Multidecadal Oscillation’s warm phase transition after 1995 and rising sea surface temperatures in the GoM were also deemed notable. Conspicuously, the paradigm shift timing was coincident with effective implementation of annual catch limits due to the 1996 Sustainable Fisheries Act, highlighting the importance of the robust regulatory environment in this region. While these results describe the GoM fishery ecosystem’s vulnerability to shifting environmental and socioeconomic conditions, they also underscore its resources’ resilience, likely rooted in their complexity and diversity, to the rapidly evolving pressures observed throughout the study period. This work emphasizes the necessity of cautious, adaptive management strategies for large marine ecosystems, particularly in the face of climate-related uncertainties and species’ differential responses. It provides insight into the GoM fishery ecosystem’s dynamics and illustrates a transferable approach for informing ecosystem-based management strategies, sustainable practices, and decision making focused on preserving ecologically, economically, and culturally vital marine resources.